(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
The Nardelli Master Equation reveals intriguing mathematical connections to the Golden Ratio, a constant deeply embedded in geometry, number theory, and natural patterns. This study explores its profound relationships with key sectors of number theory and theoretical cosmology, unveiling a unified framework where these disciplines intersect. By analyzing modular structures, symmetry principles, and higher-dimensional formulations, we discover novel mathematical links that provide fresh insights into the quantization of space-time and the fundamental nature of physical reality. These findings pave the way for deeper explorations of the interconnected nature of mathematics and physics, with potential applications in unification theories and beyond.